2013
DOI: 10.1080/19371918.2011.592042
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Women's Knowledge and Health Beliefs about Cervical Cancer and Its Screening

Abstract: Currently little is known about Portuguese women's knowledge and beliefs about cervical cancer screening, so this information is crucial to the success of cervical cancer screening programs. The intention of this study was to describe the knowledge and beliefs of women in Portugal. In-depth, face-to-face, individual interviews were conducted. Twenty-five females were recruited, the age range was 30 to 60. The results showed a lack of knowledge on cervical cancer and the Pap smear test. From a public policy poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
2
0
3
Order By: Relevance
“…Others have reported that lack of knowledge about PAP testing is found worldwide (13,(29)(30)(31)(32)(33). Women reported not knowing about the importance of screening (14,18) and about how to obtain a Pap test (14,18).…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that lack of knowledge about PAP testing is found worldwide (13,(29)(30)(31)(32)(33). Women reported not knowing about the importance of screening (14,18) and about how to obtain a Pap test (14,18).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, overall knowledge about symptoms of cervical cancer is low to moderate (21)(22)(23). The women in our study mentioned a median level of confidence in their ability to identify symptoms of cervical cancer (2.53 out of 5), with better perception associated with higher knowledge.…”
Section: Discussionmentioning
confidence: 55%
“…A pesar que las mujeres pueden considerar que el CC es una enfermedad seria, no se perciben a sí mismas en riesgo de desarrollarlo 13,14,15,16,17 , afectando por lo tanto las conductas preventivas 18 . Lo anterior concuerda con nuestros hallazgos, ya que las mujeres adherentes perciben un mayor riesgo de desarrollo de la enfermedad, sin embargo la severidad de la misma no resulta ser un factor que afecte la adherencia.…”
Section: Discussionunclassified
“…Muchas mujeres piensan que el PAP sólo se realiza si hay síntomas 13,14,16,25 , concordando con los resultados reportados, siendo una causa que determina diferencias en la adherencia al tamizaje. Respecto de la necesidad de tener hijos o estar teniendo relaciones sexuales actualmente, si bien la mayoría responde acertadamente, el 10% que no lo hizo.…”
Section: Discussionunclassified